REQUISITOS DE FORMA DESDE LA PERSPECTIVA DEL CONTRATO DE SOCIEDAD Y TIPOS DE SOCIEDADES MERCANTILES - Calderón Burneo, Ernesto (2022)
This paper has dealt with the study of the formal requirements applicable to partnership/company agreements. The concept of “formal requirements” refers to two different groups of formal requirements: those applicable to the partnership/company agreement itself and those required to access any of the corporate types regulated by the Peruvian Company Act. Despite the close relationship between the two groups, they show a different legal basis. In the first case, the principles of private law, including freedom of form, regulate its legal framework. However, in the second case, the requirements come from a public control over the companies, which is manifested in the need to have a public deed, which must be entered in the public registry